2019
DOI: 10.1002/jcla.22901
|View full text |Cite
|
Sign up to set email alerts
|

Thymidine kinase 1 concentration in pleural effusion is a diagnostic marker and survival predictor for malignant pleural effusion

Abstract: Objective Thymidine kinase 1 (TK1) is a key enzyme in the pyrimidine salvage pathway. Increased TK1 concentration correlates with cell division. TK1 is an emerging biomarker in cancer diagnosis; however, its effectiveness in diagnosis and management for malignant pleural effusion (MPE) is unclear. We evaluated the diagnostic efficiency and prognostic value of pleural effusion TK1 (pTK1) concentration for MPE. Methods From 2013 to 2017, 210 pleural effusion samples were collected from 160 patients diagnosed wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 26 publications
(36 reference statements)
0
5
0
Order By: Relevance
“…Recently, several predictive models for patients with malignant pleural effusion or malignant pleural pericardial effusion had been published. Most of them focused on the concentration of biomarkers in the pleural effusion or serum (33)(34)(35); however, the higher cost and the variation of result owing to the different techniques (36), as well as the difficulty in collecting extra tissues in patients with poor physical condition, limited the application of these predictive models (37). Tian et al used the data of NSCLC patients with malignant pleural effusion or pericardial effusion from SEER database between 2010 and 2015 to developed a nomogram, which included age, gender, race, primary site, histology type, TN status, and effusion patterns with a C-index of 0.736 (38).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, several predictive models for patients with malignant pleural effusion or malignant pleural pericardial effusion had been published. Most of them focused on the concentration of biomarkers in the pleural effusion or serum (33)(34)(35); however, the higher cost and the variation of result owing to the different techniques (36), as well as the difficulty in collecting extra tissues in patients with poor physical condition, limited the application of these predictive models (37). Tian et al used the data of NSCLC patients with malignant pleural effusion or pericardial effusion from SEER database between 2010 and 2015 to developed a nomogram, which included age, gender, race, primary site, histology type, TN status, and effusion patterns with a C-index of 0.736 (38).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, several predictive models for patients with malignant pleural effusion or malignant pleural pericardial effusion had been published. Most of them focused on the concentration of biomarkers in the pleural effusion or serum ( 33 35 ); however, the higher cost and the variation of result owing to the different techniques ( 36 ), as well as the difficulty in collecting extra tissues in patients with poor physical condition, limited the application of these predictive models ( 37 ). Tian et al.…”
Section: Discussionmentioning
confidence: 99%
“…Several predictive models for survival in MPE or MPCE have been published; however, a number of these are based on biomarker concentrations in the serum and/or in the effusion (6,7,16). In addition to the difficulty in accessing a sufficient effusion sample in patients with a poor physical status or a low effusion volume, the biomarker concentration in a sample can vary due to different measurement techniques (17).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, tissue staining for TK1 has been used to identify activated tumor vessels involved in angiogenesis in colorectal cancer (CRC) patients; indeed, in studies involving double immunostaining for both CD31 and TK1, results showed TK1 to be a highly specific marker for activated vessels [ 106 ]. Tian et al [ 107 ] demonstrated the diagnostic and prognostic capabilities of TK1 concentrations over those of other biomarkers in malignant pleural effusion (MPE), especially when compared to parallel biomarker readings of benign pleural effusion (BPE). Within their study, Tian et al compared pleural TK1 to the measurement of serum TK1 levels in 210 patients whose samples were classified as MPE or BPE.…”
Section: Tk1 As a Tumor Biomarkermentioning
confidence: 99%